Further Mathematics Study Mode

Try this quiz in CBT Mode
Further Mathematics in CBT Mode

Please share this quiz link to your friends, they might need it!

Quiz link
Share Further Mathematics with your friends
Share to WhatsApp Share Quiz CBT mode Study mode copy link
https://quizzerweb.com.ng/quiz?q=Further%2BMathematics&id=328

Join Discuss Share Question Share to WhatsApp
Question 1 Further Mathematics | WAEC/GCE (2018)
A
\(\frac{1}{2}\) 
B
C

\(2\sqrt{3}\)

 
D
Explanation.
Share Answer

\(\frac{\sqrt{3}}{\sqrt{3} - 1} + \frac{\sqrt{3}}{\sqrt{3} + 1}\)

= \(\frac{\sqrt{3}(\sqrt{3} + 1) + \sqrt{3}(\sqrt{3} - 1)}{(\sqrt{3} - 1)(\sqrt{3} + 1)}\)

= \(\frac{3 + \sqrt{3} + 3 - \sqrt{3}}{3 + \sqrt{3} - \sqrt{3} - 1}\)

= \(\frac{6}{2} = 3\)


Correct Option:
B
Join Discuss Share Question Share to WhatsApp
Question 2 Further Mathematics | WAEC/GCE (2018)
A
\({x : x \in R, x = \frac{1}{2}}\) 
B
\(x: x \in R, x\neq \frac{1}{3}\) 
C
\(x : x \in R, x = \frac{1}{3}\) 
D
\(x: x \in R\) 
Explanation.
Share Answer

The domain of a function refers to the regions where the function is defined or has a value on a particular region.

\(\frac{4x^{2} - 1}{\sqrt{9x^{2} + 1}}\) has a domain defined on all set of real numbers because the function is defined on the set of real numbers when the denominator \(\sqrt{9x^{2} + 1} \geq 0\).

\(\sqrt{9x^{2} + 1} \geq 0 \implies 9x^{2} + 1 \geq 0\) which because of the square sign has a value for all values of x, be it negative or positive.

 


Correct Option:
D
Join Discuss Share Question Share to WhatsApp
Question 3 Further Mathematics | WAEC/GCE (2018)
A
1, 3 
B
-1, -3 
C
1, -3 
D
-1, 3 
Explanation.
Share Answer

\(f(x) = 3x^{2} - 12x + 12\) and \(f(x) = 3\)

\(\therefore f(x) = 3 = 3x^{2} - 12x + 12 \implies 3x^{2} - 12x + 12 - 3 = 0\)

\(3x^{2} - 12x + 9 = 0; 3x^{2} - 9x - 3x + 9 = 0\)

\(3x(x - 3) - 3(x - 3) = (3x - 3)(x - 3) = 0\)

3x - 3 = 0 or x - 3 = 0

\(x = 1 or 3\)


Correct Option:
A
Join Discuss Share Question Share to WhatsApp
Question 4 Further Mathematics | WAEC/GCE (2018)
A
B
C
D
Explanation.
Share Answer

\((\sqrt{x} + 1) * (\sqrt{x} - 1) = 4  \implies  \frac{\sqrt{x} + 1}{\sqrt{x} - 1} + \frac{\sqrt{x} - 1}{\sqrt{x} + 1} = 4\)

\(\frac{(\sqrt{x} + 1)(\sqrt{x} + 1) + (\sqrt{x} - 1)(\sqrt{x} - 1)}{(\sqrt{x} - 1)(\sqrt{x} + 1)}\)

= \(\frac{x + 2\sqrt{x} + 1 + x - 2\sqrt{x} + 1}{x - 1} \implies \frac{2x + 2}{x - 1} = 4\)

\(2x + 2 = 4x - 4  \therefore 4x - 2x = 2x = 2 + 4= 6\)

\(x = 3\)


Correct Option:
D
Join Discuss Share Question Share to WhatsApp
Question 5 Further Mathematics | WAEC/GCE (2018)
A
\(\frac{5\sqrt{10}}{4}\) 
B
\(4\sqrt{10}\) 
C
\(5\sqrt{10}\) 
D
\(\frac{4\sqrt{10}}{5}\) 
Explanation.
Share Answer

\(4x^{2} + 5kx + 10 = (2x + \sqrt{10})^{2}\)

Expanding the right hand side equation, we have

\(4x^{2} + 4x\sqrt{10} + 10\)

Comparing with the left hand side, we have

\(5k = 4\sqrt{10}  \implies k = \frac{4}{5}\sqrt{10}\)


Correct Option:
D
Join Discuss Share Question Share to WhatsApp
Question 6 Further Mathematics | WAEC/GCE (2018)
A
-17 
B
-7 
C
D
13 
Explanation.
Share Answer

\(f(x) = 3x^{3} - 2x^{2} + 7x + 5\). 

\(x - 1 = 0, x = 1\)

\(f(1) = 3(1)^{3} - 2(1)^{2} + 7(1) + 5 = 13\)


Correct Option:
D
Join Discuss Share Question Share to WhatsApp
Question 7 Further Mathematics | WAEC/GCE (2018)
A
\(Q \cap R = \varnothing\) 
B
\(R \subset P\) 
C
\((R \cap P) \subset (R \cap U)\) 
D
\(n(P' \cap R) = 2\) 
Explanation.
Share Answer

All the statements are false except option C.

\(R \cap P = {3, 5, 7} and R \cap U = {2, 3, 5, 7, 11}\) 

\(\therefore (R \cap P) \subset (R \cap U)\)


Correct Option:
C
Join Discuss Share Question Share to WhatsApp
Question 8 Further Mathematics | WAEC/GCE (2018)
A
\(a = b^{3} - 3\) 
B
\(a = b^{3} - 9\) 
C
\(a = 9b^{3}\) 
D
\(a = \frac{b^{3}}{9}\) 
Explanation.
Share Answer

\(\log_{3}a - 2 = 3\log_{3}b\)

Using the laws of logarithm, we know that \( 2 = 2\log_{3}3 = \log_{3}3^{2}\)

\(\therefore \log_{3}a - \log_{3}3^{2} = \log_{3}b^{3}\)

= \(\log_{3}(\frac{a}{3^{2}}) = \log_{3}b^{3}   \implies  \frac{a}{9} = b^{3}\)

\(\implies a = 9b^{3}\)


Correct Option:
C
Join Discuss Share Question Share to WhatsApp
Question 9 Further Mathematics | WAEC/GCE (2018)
A
\(2x^{2} - 9x + 15 = 0\) 
B
\(2x^{2} - 9x + 13 = 0\) 
C
\(2x^{2} - 9x - 13 = 0\) 
D
\(2x^{2} - 9x - 15 = 0\) 
Explanation.
Share Answer

Note: Given the sum of the roots and its product, we can get the equation using the formula:

\(x^{2} - (\alpha + \beta)x + (\alpha\beta) = 0\). This will be used later on in the course of our solution.

Given equation: \(2x^{2} - 5x + 6 = 0; a = 2, b = -5, c = 6\).

\(\alpha + \beta = \frac{-b}{a} = \frac{-(-5)}{2} = \frac{5}{2}\)

\(\alpha\beta = \frac{c}{a} = \frac{6}{2} = 3\)

Given the roots of the new equation as \((\alpha + 1)\) and \((\beta + 1)\), their sum and product will be

\((\alpha + 1) + (\beta + 1) = \alpha + \beta + 2 = \frac{5}{2} + 2 = \frac{9}{2} = \frac{-b}{a}\)

\((\alpha + 1)(\beta + 1) = \alpha\beta + \alpha + \beta + 1 = 3 + \frac{5}{2} + 1 = \frac{13}{2} = \frac{c}{a}\)

The new equation is given by: \(x^{2} - (\frac{-b}{a})x + (\frac{c}{a}) = 0\)

= \(x^{2} - (\frac{9}{2})x + \frac{13}{2} = 2x^{2} - 9x + 13 = 0\)


Correct Option:
B
Join Discuss Share Question Share to WhatsApp
Question 10 Further Mathematics | WAEC/GCE (2018)
A
\(\frac{x}{2(x - 2)} - \frac{5}{(x - 2)^{2}}\) 
B
\(\frac{5}{(x - 2)} + \frac{x}{2(x - 2)^{2}}\) 
C
\(\frac{1}{2(x - 2)} + \frac{5x}{2(x- 2)^{2}}\) 
D
\(\frac{-1}{2(x - 2)} + \frac{8x}{2(x - 2)^{2}}\) 
Explanation.
Share Answer

\(\frac{3x - 1}{(x - 2)^{2}} = \frac{A}{(x - 2)} + \frac{Bx}{(x - 2)^{2}}\)

\(\frac{3x - 1}{(x - 2)^{2}} = \frac{A(x - 2) + Bx}{(x - 2)^{2}}\)

Comparing, we have

\(3x - 1 = Ax - 2A + Bx  \implies -2A = -1;  A + B = 3\)

\(\therefore A = \frac{1}{2}; B = \frac{5}{2}\)

= \(\frac{1}{2(x - 2)} + \frac{5x}{2(x - 2)^{2}}\)


Correct Option:
C
Next Page
Question Map